Better ceramics through colloid chemistry. Issue 3 (March 2020) - Moreno, Rodrigo
Abstract: In this work, the key role of colloid chemistry in the development of novel processing routes for ceramic manufacture is reported. An overview of the origins of a ceramic processing science is presented, emphasizing the pioneering works and the scientific fundaments of all processing steps that make use of suspensions. A brief review of the importance of colloid chemistry in the synthesis of nanoparticles with controlled purity, size and shape is given, followed by a description of the suspension properties and their effect in the beneficiation and shaping of ceramics. The main shaping techniques for the production of bulk parts, substrates and coatings and layered ceramics are shown, as well as the multiple possibilities for the design of composites with tailored microstructures and microarchitectures.